2010
DOI: 10.2106/jbjs.i.01482
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Based on Race, Ethnicity, and Sex Between Academic Orthopaedic Surgery and Other Specialties

Abstract: Our findings suggest that on a comparative basis, orthopaedic surgery lags behind general surgery and other surgical and nonsurgical fields in terms of the representation of minorities and women. Thus, given similar capabilities and qualifications of applicants, a concerted effort could be made to recruit more diverse residents and faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 9 publications
2
147
1
2
Order By: Relevance
“…Pre/post program survey results indicate that MSOP substantively and positively shifts participants' intellectual interest in orthopaedics as well as their perceptions of the profession in terms of lifestyle, workforce diversity, and competitiveness. Prior work has shown that women medical students view orthopaedics more negatively on these particular issues than their male counterparts [6,7]. MSOP appears to positively shift these perceptions, at least in the short term, which may lead to the higher than average residency match rate for program alumnae.…”
Section: -Point Likert Scalementioning
confidence: 93%
See 3 more Smart Citations
“…Pre/post program survey results indicate that MSOP substantively and positively shifts participants' intellectual interest in orthopaedics as well as their perceptions of the profession in terms of lifestyle, workforce diversity, and competitiveness. Prior work has shown that women medical students view orthopaedics more negatively on these particular issues than their male counterparts [6,7]. MSOP appears to positively shift these perceptions, at least in the short term, which may lead to the higher than average residency match rate for program alumnae.…”
Section: -Point Likert Scalementioning
confidence: 93%
“…The survey examined each participant's intention to pursue orthopaedic surgery, intellectual interest in the subject matter (orthopaedics, surgery, and musculoskeletal care), and perceptions about the field of orthopaedic surgery. The latter focused specifically on issues that were identified in a 1963 prior study [6] (nine of 37) are now ''likely'' or ''very likely'' to pursue orthopaedic residency with an additional 66% (24 of 37) stating that they were neutral on pursuing orthopaedics. Pre/post program survey data also indicated that the MSOP influenced students' perceptions of the orthopaedics profession as well as overall intellectual interest in the field.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On top of that, few arthroplasty studies explicitly considered the impact of race on outcomes, and most of them are small [1,4] . According to a 2014 Journal of Bone and Joint Surgery editorial [10], in a search for Journal of Bone and Joint Surgery articles over the past 10 years, only three articles mentioned race in the title [8,10,21] although many studies mentioned these in the text. Race was infrequently the main subject of study.…”
Section: Introductionmentioning
confidence: 99%